2010
DOI: 10.1007/s10577-010-9111-5
|View full text |Cite
|
Sign up to set email alerts
|

Integration of exogenous DNA into mouse embryonic stem cell chromosomes shows preference into genes and frequent modification at junctions

Abstract: Chromosomal integration of exogenous DNA in mammalian cells allows stable gene expression for a variety of biological applications. Although it is presumably mediated by DNA repair machinery, little is known regarding site preferences and other characteristics. We isolated and analyzed 256 chromosomal-plasmid DNA integration junctions from 158 plasmid integrants after electroporation in mouse embryonic stem (ES) cells. The frequency of integrations in transcription units (40%) showed a slight but significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…However, a more likely possibility for LIG4-independent integration may be a synthesis-dependent microhomology-mediated end-joining (SD-MMEJ) mechanism, as proposed by Yu and McVey [22]. This model well explains frequent terminal modifications observed at plasmid-genome junctions in random integrants from mouse ES cells [23] as well as little or no apparent junctional microhomologies in LIG4 -null cells ([21]; our unpublished observations).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…However, a more likely possibility for LIG4-independent integration may be a synthesis-dependent microhomology-mediated end-joining (SD-MMEJ) mechanism, as proposed by Yu and McVey [22]. This model well explains frequent terminal modifications observed at plasmid-genome junctions in random integrants from mouse ES cells [23] as well as little or no apparent junctional microhomologies in LIG4 -null cells ([21]; our unpublished observations).…”
Section: Resultsmentioning
confidence: 52%
“…Moreover, SINEs tend to distribute in gene-rich GC-rich regions, while LINEs in gene-poor AT-rich regions [30]. In this regard, recent work has reported that integration of exogenous DNA into mouse ES cell chromosomes shows preference into genes [23]. Alternatively or additionally, as LINEs present in the targeting vectors are short fragments (<300 bp)(Figure S1 in File S1), these LINE fragments may lack the ability to facilitate random integration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1b). Consistent with the intrinsic complexity of RI events38, the precise mechanisms for several junctions associated with templated insertions were difficult to interpret (Supplementary Data 1), but some junctions showed a simple pattern of templated insertions (that is, ≥6-bp direct or inverted repeats), including those copied sequences from the other side of the vector-genome junctions (Fig. 1e).…”
Section: Resultsmentioning
confidence: 94%